Therapeutic decisions in a cohort of patients with idiopathic pulmonary fibrosis: a multicenter, prospective survey from Poland. (August 2022) - Górska, Katarzyna; Maskey-Warzęchowska, Marta; Barnaś, Małgorzata; Białas, Adam; Barczyk, Adam; Jagielska-Len, Hanna; Jassem, Ewa; Kania, Aleksander; Lewandowska, Katarzyna; Majewski, Sebastian; Martusewicz-Boros, Magdalena M.; Piotrowski, Wojciech J.; et al.
Background: Pirfenidone and nintedanib are considered as the standard of care in idiopathic pulmonary fibrosis (IPF), but there is no consensus as to which of these two agents should be regarded as first-line treatment. Objective: To provide real-world data on therapeutic decisions of pulmonary specialists, particularly the choice of the antifibrotic drug in patients with IPF. Methods: This was a multicenter, prospective survey collecting clinical data of patients with IPF considered as candidates for antifibrotic treatment between September 2019 and December 2020. Clinical characteristics and information on the therapeutic approach were retrieved. Statistical evaluation included multiple logistic regression analysis with stepwise model selection. Results: Data on 188 patients [74.5% male, median age 73 (interquartile range, 68–78) years] considered for antifibrotic therapy were collected. Treatment was initiated in 138 patients, while 50 patients did not receive an antifibrotic, mainly due to the lack of consent for treatment and IPF severity. Seventy-two patients received pirfenidone and 66 received nintedanib. Dosing protocol ( p < 0.01) and patient preference ( p = 0.049) were more frequently associated with the choice of nintedanib, while comorbidity profile ( p = 0.0003) and concomitant medication use ( p = 0.03) were more frequently associated with the choice of pirfenidone. Age ( p = 0.002), lung transfer factor for carbon monoxide (TLCO ) ( p = 0.001), and gastrointestinal bleeding ( p = 0.03) were significantly associated with the qualification for the antifibrotic treatment. Conclusion: This real-world prospective study showed that dose protocol and patient preference were more frequently associated with the choice of nintedanib, while the comorbidity profile and concomitant medication use were more frequently associated with the choice of pirfenidone. Age, TLCO, and history of gastrointestinal bleeding were significant factors influencing the decision to initiate antifibrotic therapy.